A comparative analysis of multi-criteria decision-making methods - Ceballos, Blanca; Lamata, María Teresa; Pelta, David A. (Progress in artificial intelligence, 2016)
In this work, we empirically compare the rankings produced by several multi-criteria decision-making methods. We analyzed multi-MOORA, TOPSIS and three different settings for VIKOR. Using decision matrices with different number of alternatives and criteria, we compared the rankings produced using the Spearman’s correlation coefficient index. Our results showed that VIKOR could fail to obtain a ranking due to the failure of certain calculations. The rankings produced by TOPSIS and multi-MOORA were very similar, while the rankings produced by the different VIKOR variants showed a great variability.